Artificial Intelligence in Pathology - Chang, Hye Yoon (J Pathol Transl Med, 2019)
As in other domains, artificial intelligence is becoming increasingly important in medicine. In particular, deep learning-based pattern recognition methods can advance the field of pathology by incorporating clinical, radiologic, and genomic data to accurately diagnose diseases and predict patient prognoses. In this review, we present an overview of artificial intelligence, the brief history of artificial intelligence in the medical domain, recent advances in artificial intelligence applied to pathology, and future prospects of pathology driven by artificial intelligence.